Effects of the Mother’s Day Superstorm (10–11 May 2024) over the Global Ionosphere - Krishnendu Sekhar Paul; Mefe Moses; Haris Haralambous; Christina Oikonomou (Remote Sensing)
The present study examines the global ionospheric response to the “Mother’s Day Superstorm” (10–11 May 2024), one of the most intense geomagnetic storms since 1957, with a minimum SYM-H index of −436 nT. Constellation Observing System for Meteorology, Ionosphere, and Climate-2 (COSMIC-2) Radio Occultation (RO) data indicated an increase in the F2 layer maximum critical frequency (foF2) over midlatitude dayside regions, which was accompanied by a significant F-region uplift (hmF2 increase) on a global scale, even on the nightside during the main and recovery phases. At the same time, a decrease in foF2 was observed on the nightside. High southeastward and vertical drift velocities were observed in the nightside sector of the northern hemisphere with the dayside sector exhibiting upward and southwestward-to-northwestward drifts during the main and recovery phases of the storm. An intense upward drift (~170 m/s) in the southern hemisphere was registered with the poleward expansion of the Equatorial Ionization Anomaly (EIA) during the main phase. Swarm A data highlighted the EIA expansion from ~45°N to 60°S during the dayside main phase and from ~30°N to 40°S on the nightside during recovery.